On the Iranian English as Foreign Language Novice and Experienced Teachers’ Attributional Styles and Professional Identity - Kalali Sani, Seyed Farzad; Motallebzadeh, Khalil; Khodabakhshzadeh, Hossein; Zeraatpisheh, Mitra (Frontiers in Psychology, 2022)
Teacher professional identity (TPI) is a characteristic of a teacher, which should be developed in a long, consistent, and progressive process and usually shapes in any specific educational and social context. In addition to several factors influencing TPI, such as university education and empowerment courses, experience seems to play a significant role. Moreover, the role of psychological factors is highly undeniable in the formation and development of TPI. Attributional style (AS) is defined as the consistent way by which people can explain the reasons for the occurrence of good or bad events. Besides considering ASs as one of the crucial variables for academic success, it can be regarded as one of the aspects of shaping one’s identity in general and the teacher’s identity in particular. In order to study the relationship between AS and TPI of teachers regarding their experience, two questionnaires were distributed among 317 Iranian English as foreign language (EFL) teachers, and about 80% returned them. The researchers ran correlational analyses and they came up with a positive and significant relationship (p = 0.04) between TPI and teacher attributional styles (TASs) of teachers. Moreover, experienced teachers proved to have a significant difference from novice teachers regarding their TPIs. The findings of this study would hopefully be advantageous for teacher educators to educate pre-service teachers by ways of constructing identity, and they may be applicable for Iranian EFL teachers to know and focus on different aspects of their professional identity. Moreover, they learn how to manage the intervening factors and shape and empower different domains of their PI, such as teaching experience, by means of exploring and knowing their ASs.